2017
DOI: 10.1097/md.0000000000006621
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal shock wave therapy is effective in treating chronic plantar fasciitis

Abstract: Background:Plantar fasciitis (PF) is the most common reason for heel pain. The efficacy of extracorporeal shock wave therapy (ESWT) as an ideal alternative to conservative treatments and surgery is controversial, and almost all previous articles compared general ESWT with placebo without indicating the kind of shock wave. We undertook a meta-analysis to compare the efficacy of general ESWT, focused shock wave (FSW), and radial shock wave (RSW) with placebo, to assess their effectiveness in chronic PF.Methods:T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
65
0
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(75 citation statements)
references
References 49 publications
3
65
0
7
Order By: Relevance
“…Whereas US is considered a reliable and inexpensive imaging technique for assessing PF thickness (23) . The efficacy of ESWT in the treatment of PF was investigated in a large number of randomized controlled trials (RCT) (16,24,25) In the present study, the ESWT group showed significant improvement in all clinical parameters after one month of treatment, 56.52% of the patients reported a ≥ 50% improvement in the FFI, 90.5% of the patients reported a ≥ 30% reduction in the pain score and the plantar fascia thickness was reduced in 86.95% of the patients. A meta-analysis was done in 2013 to investigate the efficacy of ESWT compared to placebo in the treatment of chronic PF and reported a > 60% reduction in pain scores and improvement in Roles-Maudsley score (RMS) which is a patient-administered scoring system regarding activity limitations.…”
Section: Discussionmentioning
confidence: 71%
“…Whereas US is considered a reliable and inexpensive imaging technique for assessing PF thickness (23) . The efficacy of ESWT in the treatment of PF was investigated in a large number of randomized controlled trials (RCT) (16,24,25) In the present study, the ESWT group showed significant improvement in all clinical parameters after one month of treatment, 56.52% of the patients reported a ≥ 50% improvement in the FFI, 90.5% of the patients reported a ≥ 30% reduction in the pain score and the plantar fascia thickness was reduced in 86.95% of the patients. A meta-analysis was done in 2013 to investigate the efficacy of ESWT compared to placebo in the treatment of chronic PF and reported a > 60% reduction in pain scores and improvement in Roles-Maudsley score (RMS) which is a patient-administered scoring system regarding activity limitations.…”
Section: Discussionmentioning
confidence: 71%
“…Many types of well-established conservative treatments are available for plantar heel pain, such as therapeutic exercise, foot and ankle mobilization, electrical stimulation for pain reduction, taping, footwear modification, orthotics, extracorporeal shock wave therapy, and laser therapy [41][42][43][46][47][48]. Trigger point dry needling is a treatment modality commonly used by physiotherapists for the management of individuals with musculoskeletal disorders such as plantar heel pain.…”
Section: Discussionmentioning
confidence: 99%
“…Other alternative treatment options for relieving PF symptoms include laser therapy [46,47], extracorporeal shockwave therapy [48], and dry needling [49][50][51][52][53][54][55]. Trigger point dry needling is an invasive option and has been widely used as an alternative treatment for PF [56].…”
Section: Dry Needlingmentioning
confidence: 99%
“…El estudio de este tema se realizó a través de tres artículos escogidos del meta-análisis de Jiale Sun et al (18) que comparan el tratamiento con la misma dosis de frecuencia de onda (2000 impulsos) con dosis placebo a través de piezas que realizan un bloqueo en la zona anatómica impidiendo la transmisión de impulsos desde el aplicador hasta la piel. Para comparar el efecto de las ondas de choque con el efecto placebo para la fascitis plantar, los autores reparten un número n de pacientes por igual en el grupo de tratamiento y en el grupo control.…”
Section: Tratamiento Con Ondas De Choque Extracorpóreas Para Fascitisunclassified